Genomic analysis for cattle breeding improvement, progress and future perspectives in Peru: a review - Figueroa Venegas, Deyanira antonella (2025)
Genomics offers a promising solution by enabling precise cattle selection and breedingto boost productivity and sustainability. In Peru, livestock plays a crucial role in theeconomy and food security. Despite its importance, the sector faces significantchallenges, including poor pasture quality, limited conservation practices, a shortage oftrained professionals, minimal use of genomic tools, and an incomplete understandingof the genetic potential of both native and introduced breeds. Since the 1940s, Peruhas advanced in genetic improvement through artificial insemination, improved semenpreservation, the establishment of a National Semen Bank, and the introduction of newbreeds. Key developments have included embryo transfer, in vitro fertilization, andpioneering cloning efforts. Future perspectives for livestock genomics in Peru involveexpanding bioinformatics capacity, improving genomic infrastructure, and integratinggenomic selection into national breeding strategies. This review discusses the history,current status, challenges, and future perspectives of livestock genomics in Peru.